Structural And Magnetic Properties Of Rhodium Clusters - Soon,, Yee Yeen (2017)
Nanocluster has been a system of interest for the past decades due to its peculiar size-dependent properties as compared to its bulk counterparts. As far as 4d transition elements are concerned, rhodium (Rh) cluster is one of the most-debated systems. Bulk Rh is a paramagnetic material, but when it is reduced to atomic dimension, its structural and magnetic properties vary with the cluster size. This project is aimed to perform systematic study to investigate the unusual properties at the lowest energy state of RhN clusters, where N is the number of atoms ranged from 2 to 23. To study large Rh clusters, Rh26, Rh30 and Rh38 are also included in the study. The lowest-energy configurations of the clusters were obtained by performing two-stage optimization.